Impact of Galactic magnetic field modeling on searches of point sources via ultrahigh energy cosmic ray-neutrino correlations - Carpio Dumler, José Alonso (2016)
The authors gratefully acknowledge DGI-PUCP for financial support under Grant No. 2014-0064, as well as CONCYTEC for graduate fellowship under Grant No. 012-2013-FONDECYT. We also thank Esteban Roulet and Maria Teresa Dova for the useful discussions.